Production permeabilized cell mass of Kluyveromyces lactis and catalytic activity of β-galactosidase in lactose hydrolysis - Fontes, Edimar A . F. (2013)
The production permeabilized cell mass of Kluyveromyces lactis containing the enzyme bgalactosidase and her catalytic activity in the lactose hydrolysis was accomplished. For obtaining of the permeabilized cell mass, cells were produced, growing in serum of UF sterile milk. To promote the permeabilization of the membrane, cells were treated with ethanol solution 50% to facilitate the contact between the enzyme and the substratum in the process lactose hydrolysis. The catalytic activity of the enzyme in the lactose hydrolysis was obtained by the lineal relationship between the reaction speed and dry weight in mg of permeabilized cell. The mass of 1mg of permeabilized cells was equal to 0.32 units of enzyme activity. The effect of the suspension of permeabilized cell in the initial speed of reaction was studied using different lactose concentrations (1, 40, 100 and 140 mM) and suspensions of permeabilized cells that varied from 0.1 to 3 mg/ ml.The reactions were accompanied in the spectrophotometer DU in 510nm, that it supplied a curve of the absorbance variation with the time of reaction. The inclination of the straight line presented by each curve corresponded the initial speeds for each concentration of permeabilized cell and lactose. It was used in that analysis a reagent colorimeter GOP-PAP that specifically reacted with the present glucose in the middle. For conversion of the absorvance reading in units of mM glucose, it was made a curve standard of glucose. The suspension of 1mg/ml of permeabilized cell added to the reaction mixture, it was selected by her lineal relationship with the reaction speed for minimum concentrations (1mM) and extreme (140 mM) of lactose. Values below 1mg/ml were appropriate for the lineal reaction between speed and initial concentration of enzyme.